The use of artificial intelligence in islamic religious education at higher education institutions: An analysis of opportunities and challenges - S, Waway Qodratulloh; Suhartini, Ida; Rahman, Rini (Universitas Negeri Padang, 2023)
This scientific article explores the implementation of Artificial Intelligence (AI) in Islamic Religious Education (PAI) learning at higher education institutions, focusing on the analysis of existing opportunities and challenges. This topic is crucial to study, not only because no one has done it before, but this study is a step to understand how technology can be effectively used in the context of islamic religious education at the higher education. On the other hand, this study is also conducted to identify potential areas for further research and the development of innovative solutions in addressing existing challenges. The method used in this research is qualitative descriptive. Data were collected through the interview process with lecturers and students, as well as literature studies through Syllabus, RPS, and PAI Teaching Materials. Additionally, a study of various supporting literature in the form of journals, books, and reports of other research results was also conducted. From the results of the study, four main opportunities were found to improve the quality of the implementation of religious education and character for students, namely more personal learning experiences, improved quality of materials, material improvement, and learning simulations. AI can facilitate a more adaptive and responsive learning experience to individual needs and allow for the development of richer and more in-depth materials. However, the implementation of AI also faces significant challenges, including ethical issues and religious sensitivity, resource availability, apathy and resistance to technology, and assurance of content quality.